The influence of self-esteem, depression, and life satisfaction on the future expectations of Peruvian university students - Mamani-Benito, Oscar; Carranza Esteban, Renzo Felipe; Caycho-Rodríguez, Tomás; Castillo-Blanco, Ronald; Tito-Betancur, Madona; Alfaro Vásquez, Rosa; Ruiz Mamani, Percy G. (Frontiers in Education, 2023)
Strengthening the self-confidence of future professionals can help in achieving professional goals with a likelihood of being able to achieve them in the future. The objective was to determine whether self-esteem, depression, and life satisfaction influence the future expectations of Peruvian university students. A total of 708 university students participated (64.8% were female, mean age = 21.49; SD = 4.83). The Rosenberg Self-Esteem Scale, the Patient Health Questionnaire-2, the Life Satisfaction Scale, and the Adolescent Future Expectations Scale were used. A structural equation modeling was employed to test the impact of self-esteem, depression, and life satisfaction on future expectations. The model relating the study variables demonstrated an adequate fit (p < .001, CFI = .940, RMSEA = .073), confirming the relationship between self-esteem (β = .33, p < .001), life satisfaction (β = .28, p < .001), and depression (β = -.14, p = .010.) with future expectations. This model explained 36% of future expectations. In conclusion, the future expectations may be affected by low levels of self-esteem and life satisfaction and high levels of depression.